Intended Publication: Journal’s Of Exploring Educational Competencies: A Comparative Analysis Of Pisa And Pirls Studies - Sulistyaningrum, Dyah (International Journal of Science, Technology & Management, 2024)
The paper provides a comparison review of the role of PISA (Program for International Student Assessment) and PIRLS (Progress in International Reading Literacy Study) arranged by OECD (Organisation for Economic Co-operation and Development) in the development of Indonesian Education System. Based on the criteria outlined in the preliminary examinations, relevant articles were included in this review study. The research methods used for examination were descriptive and content analysis. Specifically, content analysis was employed to analyze studies that focused on the rankings of ASEAN countries as well as the declining score trends of Indonesia in the PISA and PIRLS. As a result, The Tables of ASEAN countries Educational Developments and Comparison are presented. With this study, the role of PISA and PIRLS can be determined and further measurements can be taken by major stakeholders in Indonesian Educational Territory.